Assessing the status of Schizophrenic patients in Shafa psychiatric center in Rasht (1999) - Salman Ghasem, K (Iran University of Medical Sciences, 1999)
Psychiatric diseases are one of the oldest and well known diseases that many scientific and medical solutions are presented about treatment of them. Among psychiatric diseases, schizophrenia is one of the important diseases that are special for humanity. Schizophrenia is a mental disease that has many signs and symptoms in thought, perception, excitement, and also, have observable behavioral disturbances. These presentations are combined to each other in multiform shapes. Hence, clinical manifestation, therapeutic response and disease progress in these patients are very various and this is complicating its diagnosis. Adolescence is the most sensitive period of human life and schizophrenia as an unpleasant phenomenon invades to this period and deteriorates growth and productivity. Near the 50% of capacity of the psychiatric hospitals are occupied by schizophrenic patients. Therefore, regarding many problems occurred for patient, family and society, specific and timely planning is very important